Research progress on compounding agent and mechanical test method of fluororubber. Issue 36 (29th April 2021) - Xu, Zehua; Zhang, Yanbin; Li, Anling; Wang, Jiwen; Wang, Guangfei; He, Qiang
Abstract: Fluororubber (FKM) materials have excellent mechanical properties, and are widely used in automotive and aerospace fields. As fluorine rubber is a typical representative of new special rubber, the formula and mechanical test method of fluorine rubber have become one of the important issues at present. Multi‐factor optimization of fluororubber compound plays an important role in the mechanical properties of FKM. Based on the introduction of new materials in FKM compounding agents (reinforcing agent, softening plasticizer, anti‐aging agent, accelerator, vulcanizing agent, auxiliary agent and filler), this paper focuses on the research progress of characterization methods and mechanical properties of the composite materials combined with FKM. Abstract :